Does Green Public Procurement lead to Life Cycle Costing (LCC) adoption?. Issue 3 (June 2019) - De Giacomo, Maria Rosa; Testa, Francesco; Iraldo, Fabio; Formentini, Marco
Abstract: Life Cycle Costing (LCC) is rarely used in public procurement and public institutions have yet to fully understand its potential value for sustainable procurement. The new European Directive on Public Procurement is, however, designed to position LCC as central to sustainable sourcing. Although previous studies have identified positive correlations between Green Public Procurement Policies (GPP) and LCC, it is still unclear how public institutions can further adopt LCC practices by leveraging their experience of green sourcing. In this study an organizational learning theoretical perspective is taken to investigate the circumstances under which public administrations' experience of GPP – considered as a way of integrating the dimension of environmental sustainability into the sourcing process – stimulates their LCC learning and capabilities – considered as a way to include the sustainability economic dimension. The goal is to understand if the adoption of GPP can stimulate the internalisation of LCC in public tenders. A multinomial logistic regression was conducted using a sample of 120 public administrations located in different countries. The results show that experience of GPP stimulates the internalisation of LCC at a public level, but only under specific conditions. The study contributes to the Sustainable Supply Management literature, being one of the first studies in the field adopting an organizational learning theoretical lens to review the role of experience as significant opportunity to develop capabilities. It also contributes to the organizational learning theory, by confirming that experience can aid learning but only in specific environmental contexts. Highlights: Experience in Green Public Procurement can enable Life Cycle Costing internalisation. Contexts characterized by high barriers against LCC adoption benefit from GPP experience. GPP experience stimulates the integration of environmental and economic dimensions of sustainability. We provide key implications for public administrations in understanding the value of GPP. We underline the critical role of organizational learning for public administrations.